AN EXPLORATION OF CUSTOMERS’ SWITCHING BEHAVIOR IN ISLAMIC BANKING INDUSTRY - Rama, Ali (Journal of Islamic Monetary Economics and Finance, 2017)
The existence of the switching behavior among Islamic bank customers may affect to the survival of the Islamic banks of the country. Switching behavior is mostly as an outcome of the negative service experience that may be related to several factors. The purpose of the study is to provide an insight of the drivers that lead to a bank customer switching behavior from one Islamic bank to another bank. The study employed survey method through questionnaire instrument and distributed to Islamic banking customers in several areas of Banten Province, Indonesia. The result of statistical analysis shows that customer satisfaction, service quality, shariah compliance, prices and involuntary switching have their significant effect on customers’ switching behavior in the Islamic banks. However, service failure and advertisement are not statistically significant in driving bank switching. Therefore, the Islamic bank manager should shape their business model around customers’ needs and focuses operational improvements on customers’ most valued interactions.